Analysis of mathematics test items quality for high school - Budi Manfaat; Ayu Nurazizah; Muhamad Ali Misri (Graduate School, Universitas Negeri Yogyakarta, 2021)
This study aims to determine the quality of the mathematics test items at high school in terms of validity, reliability, differentiation, difficulty level, and distractor effectiveness. This study is an evaluation type of research with a quantitative approach. The subjects in this study were 44 class XII students of SMKN 3 Kuningan and 39 class XII students of SMAN 1 Jalaksana. The results show that the majority (96.67%) of the items are declared valid in content by the experts. The test has very high reliability (0.90). The items have the ideal difficulty level. Most of the questions (70%) have medium difficulty, a few questions (6.67%) are very easy, and a few questions (20%) are difficult, and (3.3%) are very difficult. Most of the items (83.33%) have good discriminating power, and only a few questions (16.67%) have poor discriminating power. Most (90%) of the questions have a well-functioning answer choice, and only a few questions (10%) have the answer choice not functioning properly. Overall, this study can be concluded that the Mathematics Test Questions at SMKN 3 Kuningan are of good quality.